PP.LB02.15: COMBAT ASIST- 2013–2015- HYPERTENSION EDUCATIONAL PROGRAM DEDICATED TO ROMANIAN NURSES. (June 2015) - Herdea, V.; Paun, E; Brinza, I; Udrescu, M; Stoica, D; Dorobantu, M
Abstract : Objective: Increasing number of hypertension cases in global population, regardless geographical location, origin, sex, age, ethnicity, considering that health systems have been developed in last years, access and affordability to healthcare have been improved, raise practical problems: Risk factors impact in hypertension development. Informational pressure above healthcare providers Educational activity requirements to develop an active partnership between patient and medical staff. Implementing a modern interactive educational Program regarding hypertension patients care, dedicated for nurses. Hypertension concept from theory to practice. Risk factors. Internal protocol for holistic/integrative hypertension patient approach. Blood pressure measuring algorithm/ HBPM-"home blood pressure measuring" concept/ Optimized lifestyle changing patient counseling. Design and method: Combat Asist-is a National modern Project which bring up-dated medical information, dedicated to nurses. developed between 2013–2015 in 14 major cities of Romania including 1100 participants. We have been prepared interdisciplinary medical teams with physicians, nurses and psychologists. All they have similar training for hypertension patients care: age, gender, urban/rural areas, specialty, reasons which led to program participation. Combat Asist were included interactive workshops: Hypertension management High risk Hypertension Families Patient counselling with the aim of helping to understand and to become an active partner involved in the care of his own health. Results: Key points of the workshops: monitoring algorithm for home blood pressure measurement(HBPM) early detection, compliance to treatment, psycho-behavioral characteristic of chronic cardiac patients, the impact of hypertension disease inside the family relationships. The project was held under the aegis of the Romanian Society of Hypertension, the first of its kind in Eastern Europe. Conclusions: Hypertension- "the silent killer"-major public health problem, complex implications at individual, family and society level in the same time. Correct, continuous patient monitoring by qualified medical staff care, the high risk hypertension families, allow to avoid/delay the severe comorbidities, disability, death, high social costs that accompany hypertension disease. Active involvement of the patient in his own health supervision by HBPM- lead to better long-term outcomes of the disease and improve quality of life.